Legislative Gaps in the Anti-Money Laundering Policy of the Republic of Uzbekistan - Akhadjon Yuldoshev (Zien Journals, 2022)
The present work analyzes some of the gaps in the national policy of the Republic of Uzbekistan in the field of combating the crime of money laundering. The article highlights the negative consequences of the lack of criminalization of insider trading and market manipulation, and some issues surrounding initiating criminal investigation of the crime of money laundering. It is concluded that if the Republic of Uzbekistan aims to have a strong national anti-money laundering policy, it needs to comply with the international standards of the inter-governmental organization FATF (Financial Action Task Force)
Keywords: money laundering; insider trading; market manipulation; crime